The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/jcal.12149
|View full text |Cite
|
Sign up to set email alerts
|

Instructor accents in online education and their effect on learning and attitudes

Abstract: Reductions in perceptual fluency have been shown to negatively impact attitudes towards learning material, but not learning itself. The current study extends this work to spoken presentations and examines whether the presence of a foreign accent negatively affects learners' experience in an online learning environment. Results indicate that the presence of an instructor accent, consistent with prior work on perceptual fluency, does not impact learning, but does cause learners to rate the instructor as less eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 18 publications
(18 reference statements)
2
21
2
Order By: Relevance
“…Recent research extended this effect to attitudes toward an instructor in an online learning environment where instructors with accented speech were judged more negatively despite the fact that learning outcomes for students did not differ between instructors with and without accent (Sanchez & Khan, 2016).…”
Section: Fluency In Social Interactionmentioning
confidence: 99%
“…Recent research extended this effect to attitudes toward an instructor in an online learning environment where instructors with accented speech were judged more negatively despite the fact that learning outcomes for students did not differ between instructors with and without accent (Sanchez & Khan, 2016).…”
Section: Fluency In Social Interactionmentioning
confidence: 99%
“…Research examining the effects of instructor fluency rather than perceptual fluency has utilized more realistic variations in students' experience of fluency, but the setting has remained artificial (i.e., very short instructional videos with no extrinsic investment on the part of the participants; e.g., Carpenter et al, 2013;Carpenter et al, 2016;Sanchez & Khan, 2016; but see Williams & Ceci, 1997). To this end, the purpose of the present study was to determine whether instructor fluency is related to students' evaluations of their learning in an actual course, much as occurs in more contrived laboratory experiments that have examined this question (e.g., Carpenter et al, 2013;Carpenter et al, 2016;Sanchez & Khan, 2016). We found that students' ratings of instructor fluency were correlated with their judgments of learning, various ratings of their instructor, and various ratings of the course and its topics.…”
Section: Discussionmentioning
confidence: 99%
“…Although the experience of fluency in learning situations correlates with a sense (or the explicit judgment) that information has been easily acquired, it is not always correlated with actual learning (e.g., Bertsch, Pesta, Wiscott, & McDaniel, 2007;Bjork, 1994;Carpenter et al, 2013;Carpenter, Mickes, Rahman, & Fernandez, 2016;Eitel, Kuhl, Scheiter, & Gerjets, 2014;Hirshman & Bjork, 1988;Leutner, Leopold, & Sumfleth, 2009;Rhodes & Castel, 2008;Sanchez & Khan, 2016;Slamecka & Graf, 1978;Yue, Castel, & Bjork, 2013). For this reason, if students base metacognitive evaluations of their learning on how fluently or easily they processed learning materials-but that experience of fluency is not correlated with their actual learning-then their self-assessments of their learning will be inaccurate.…”
Section: Fluency and Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Such speakers were ascribed negative emotions of annoyance and irritation and labelled less intelligent and successful (Dragojevic et al, 2017). Similarly, in a study focusing on online learning, when students evaluated an instructional video narrated by the instructor who was hard to understand, they downgraded the instructor in their evaluations, expressing negative attitudes towards online coursework and evaluating video content as more difficult, even though students' actual understanding of the video was not compromised (Sanchez & Khan, 2016). In fact, a comprehensibility scale akin to that used in L2 speech research has now been validated as part of a five-item processing fluency measure, and this measure appears to explain various human judgments (truthfulness, preference, perceived risk), all attributed to processing fluency in prior literature (Graf et al, 2018).…”
Section: Comprehensibility: An Index Of Processing Fluencymentioning
confidence: 99%